1987
DOI: 10.1080/02652038709373639
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of oxytetracycline in eggs after medication of laying hens

Abstract: The kinetics of oxytetracycline elimination into eggs were determined separately for albumen and yolk after oral administration through either drinking water (0.1-0.25 and 0.5 g/l for 5 days) or feed (300 and 600 ppm for 7 days) or after intramuscular injections (3 X 15 mg/kg body weight and 3 X 30 mg/kg body weight), 24 hours apart. Residues were assayed by a microbiological agar diffusion method, with Bacillus cereus as test-organism. The detection threshold was 0.07 micrograms/g for albumen and 0.2 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

1989
1989
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 4 publications
2
9
2
Order By: Relevance
“…Frieser etal. (1986) and Roudaut et al (1987Roudaut et al ( , 1989 also found similar observations after medication via the drinking water and feed. All of these tetracyclines seem to persist longer in yolk (Nogawa et al 1981, Roudaut et al 1989.…”
Section: Residues Of Doxycycline and Oxytetracycline In Eggs Aftersupporting
confidence: 82%
See 2 more Smart Citations
“…Frieser etal. (1986) and Roudaut et al (1987Roudaut et al ( , 1989 also found similar observations after medication via the drinking water and feed. All of these tetracyclines seem to persist longer in yolk (Nogawa et al 1981, Roudaut et al 1989.…”
Section: Residues Of Doxycycline and Oxytetracycline In Eggs Aftersupporting
confidence: 82%
“…The present experiment, however, showed that mean peak concentration of OTC in the yolk, reached 2 days after withdrawal, was approximately double that reported by Nogawa et al (1981). As with the depletion period, Nogawa et al (1981) and Roudaut et al (1987) noted that OTC was detected in the yolk for 4 days after withdrawal, a much shorter period than in the present experiment. The depletion period in the albumin also lasted longer in the present experiment than in others (Nogawa et al 1981, Roudaut et al 1987).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Analytical procedures suggested in the literature for OXY detection and quantification regard microbiological methods (Jevinova et al, 2003;Gesche et al, 2001;Piriz et al, 2001;Myllyniemi et al, 2000;Okerman et al, 2001;Tantillo et al, 1997;Markakis, 1996;Wanner et al, 1994;Hasselberger, 1993;Jinbo et al, 1992;Roudaut et al, 1987;Muellerbrennecke et al, 1980) or liquid-chromatographic techniques (Khosrokhavar et al, 2008;Fletouris and Papapanagiotou, 2008;Maia et al, 2008;Kowalski and Pomorska, 2007;Biswas et al, 2007;Fritz and Zuo, 2007;Miller et al, 2007;Kowalski et al, 2006;Hosseini et al, 2006;Poapolathep et al, 2008;Yegorova et al, 2006;Pena et al, 2005;Rupp and Anderson, 2005;Lu et al, 2004;Schneider et al, 2007;Kim et al, 2006). The former is unsuitable for routine control procedures considering that each trial may take several days, and analytical laboratories also require proper facilities to handle biological compounds safely.…”
Section: Introductionmentioning
confidence: 98%
“…Little is known concerning colistin elimination in chicken eggs (6). Therefore, this study, which is part of experiments performed at the National Laboratory of Veterinary Drugs concerning antibiotic deposition in eggs (3,4,5), was undertaken to determine to what extent eggs were contaminated by colistin after oral and parenteral administration.…”
Section: Introductionmentioning
confidence: 99%